2021
DOI: 10.3390/antiox10081215
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin Inhibits NLRP3 Inflammasome by Suppressing TLR4/MD2-Mediated Mitochondrial ROS Production

Abstract: Fisetin has numerous therapeutic properties, such as anti-inflammatory, antioxidative, and anticancer effects. However, the mechanism by which fisetin inhibits NLRP3 inflammasome remains unclear. In this study, we observed that fisetin bound to TLR4 and occluded the hydrophobic pocket of MD2, which in turn inhibited the binding of LPS to the TLR4/MD2 complex. This prevented the initiation of scaffold formation by the inhibition of MyD88/IRAK4 and subsequently downregulated the NF-κB signaling pathway. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Here, we demonstrated that endometriosis in rats caused the activation of NLRP3 and NF-κB pathways as well as the increase in levels of IL-1β and TNF-α, while fisetin inhibited the activation of NLRP3/NF-κB as well as diminished the levels of IL-1β and TNF-α. These results are in agreement with several works that showed that fisetin treatment was able to reduce the NF-κB/NLRP3 pathway as well as reduce the release of proinflammatory cytokines [ 15 , 57 , 58 ].…”
Section: Discussionsupporting
confidence: 93%
“…Here, we demonstrated that endometriosis in rats caused the activation of NLRP3 and NF-κB pathways as well as the increase in levels of IL-1β and TNF-α, while fisetin inhibited the activation of NLRP3/NF-κB as well as diminished the levels of IL-1β and TNF-α. These results are in agreement with several works that showed that fisetin treatment was able to reduce the NF-κB/NLRP3 pathway as well as reduce the release of proinflammatory cytokines [ 15 , 57 , 58 ].…”
Section: Discussionsupporting
confidence: 93%
“…RAW 264.7 macrophages were seeded at a density of 1 × 10 5 cells/ml in 8-well chamber slides. Prior to exposure to LPS (500 ng/mL) for 24 h, DHP (0–25 μM) or MitoTEMPO (10 μM) was treated for 2 h. The cells were then stained with MitoTracker Green (0.5 μM) for 30 min and counterstained with 2 μM MitoSOX Red for 10 min . In parallel, LPS (0.5 mg/mL, 2 nL in each larva) or PBS was microinjected in the yolk of 3 dpf zebrafish larvae ( n = 20), and the larvae were immediately immersed in embryo medium with DHP (25 μM) or MitoTEMPO (10 μM).…”
Section: Materials and Methodsmentioning
confidence: 99%
“…RAW 264.7 macrophages were seeded at a density of 1 × 10 5 cells/mL in six-well plates and treated with 25 μM DHP, 10 μM MitoTEMPO, or 10 μM TLR4-IN-C34 for 2 h, followed by treatment with 500 ng/mL LPS for an additional 2 h. The cells were then washed with ice-cold PBS and stained using the Muse MitoPotential Kit (Luminex) for 20 min . A Muse cell analyzer was used to measure the mitochondrial membrane potential of the cells exhibiting depolarization.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…LPS is usually used to induce inflammation. The LPS+ATP-treated cells showed obvious pyroptosis, which is the classic pyroptosis model [57,58]. Here, PC12 cells were treated with LPS at different times and ATP for 1 hour to generate an inflammation-related pyroptosis model, which was utilized to assess the expression of HSF1 and NLRP3 in the classic pyroptosis model (Figure 5(a)).…”
Section: Hsf1 Negatively Regulated Nlrp3 and Pyroptosis In Pc12 Cellsmentioning
confidence: 99%